Community-based protection: the ICRC approach - Cotroneo, A; Pawlak, M (Refugee Studies Centre, University of Oxford, 2016)
The ICRC tries to ensure that its activities on behalf of IDPs and those at risk of displacement support, rather than undermine, communities’ and individuals’ self-protection mechanisms and coping strategies.